Efek Sari Buah Cherry (Prunus avium (L.) L.) terhadap Efek Sedasi dan Waktu Tidur pada Mencit Putih Jantan - Nisa Najwa Rokhmah; Yulianita Yulianita; Moh Fauzan Jauhari Suherlan (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Sedation can be defined as the use of sedative medication to relieve intolerable and refractory distress by reducing patient consciousness. Sedation can cause mild depression in the central nervous system without loss of consciousness and calming effect and prevent seizures. Cherry is a plant with sedative potential effect, contain melatonin as a flavonoid compound. This study aims to determine sedative effect, effective dose, and sleep duration in white mice male after cherry juice administration. The rotarod test was conducted to determine the resistance time of tested mice on a rotating rod. The observed parameter was the length of the time the mice running on a rotating rod at a speed of 28 rpm. Cherry juice was prepared using a juicer and then filtered with muslin cloth and dried with vacuum dryer. Cherry juice was prepared in 3 doses, they were treatment dose 1, 2, and 3 with cherry juice of 8.3, 16.6, and 25 mg/20gBW, respectively. Aquadest was used as negative control (0.5 ml/ mice), while phenobarbital was the positive control at a dose of 0.8 mg/ 20gBW). The results showed that treatment dose 3 containing 25 mg/20gBW) cherry juice was the most effective dose with the fastest falling effect (13.41 second) on rotarod and the longest duration of sleep time (45.92 minute).